Methods of Qur'an Research and Quran Tafseer Research its implications for contemporary Islamic thought: (Metodologi Tafsir Al-Qur'an) - Andri Nirwana AN; Fahmi Arfan; Fahmi Dolles Marshal; Candra Maulana; Nazar Fadli (Bulletin of Islamic Research, 2024)
This research article explores the methodologies utilized in Qur'anic research and the science of Tafseer (exegesis). The study aims to provide a comprehensive overview of the various approaches and methods applied in the interpretation and analysis of the Qur'an. By examining both classical and contemporary Tafseer, the article seeks to highlight the evolution of interpretive techniques and their relevance in modern scholarly discourse. The findings underscore the importance of methodological rigor in Qur'anic studies and its implications for contemporary Islamic thought.